2017
DOI: 10.1016/j.cub.2017.05.059
|View full text |Cite
|
Sign up to set email alerts
|

A bHLH Code for Sexually Dimorphic Form and Function of the C. elegans Somatic Gonad

Abstract: Summary How sexually dimorphic gonads are generated is a fundamental question at the interface of developmental and evolutionary biology [1–3]. In C. elegans, sexual dimorphism in gonad form and function largely originates in different apportionment of roles to three “regulatory cells” of the somatic gonad primordium in young larvae. Their essential roles include leading gonad arm outgrowth, serving as the germline niche, connecting to epithelial openings, and organizing reproductive organ development. The dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…, 2014). The arg-1 promoter, by contrast, gives a strong signal in mDTCs, but no signal in hDTCs (this paper; Sallee, Littleford, et al. , 2017).…”
Section: Resultsmentioning
confidence: 77%
“…, 2014). The arg-1 promoter, by contrast, gives a strong signal in mDTCs, but no signal in hDTCs (this paper; Sallee, Littleford, et al. , 2017).…”
Section: Resultsmentioning
confidence: 77%
“…A genome-wide approach for identifying candidate bHLH binding sites in C. elegans identified these sequences as candidate targets for HLH-2 heterodimers with 9 candidate HLH partners (HLH-3, −4, −10, −14, −15, −19, HND-1 and LIN-32) (Grove et al, 2009). Directed studies on the binding of HLH-2 have demonstrated that this sequence will also bind HLH-2 homodimers both in vivo and in vitro (Krause et al, 1997; Harfe et al, 1998; Sallee and Greenwald, 2015, Sallee et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…We assayed the effect of the CKM using null alleles for cdk-8 and cic-1 on the expression of the lag-2 transcriptional reporter arIs222[lag-2p::tagrfp], which contains 7.2 kb of 59 flanking region (Sallee and Greenwald 2015;Sallee et al, 2017). This reporter is strongly expressed in P6.p and its descendants in otherwise wild-type worms ( Figure 1B), and is expressed normally in mutants lacking the CKM components cdk-8 or cic-1 ( Figure 1C).…”
Section: Resultsmentioning
confidence: 99%